Explaining the Decline in the US Labor Share: Taxation and Automation - Burkhard Heer; Andreas Irmen; Bernd Süssmuth (Center for Economic Studies and ifo Institute (CESifo), 2022)
This study provides evidence for the US that the secular decline in the labor share is not only explained by technical change or globalization, but also by the dynamics of factor taxation, automation capital (robots), and population growth. First, we empirically find indications of co-integration for the period from the last quarter of the 20th to the first decade of the 21st century. Permanent effects on factor shares emanate from relative factor taxation. The latter also have a lasting effect on the use of robots. Variance decompositions reveal that taxing contributes to changes in the two income shares and in automation capital. Second, we analyse and calibrate a neoclassical growth model extended to include factor taxation, automation capital, and capital adjustment costs. Labor and automation capital are perfect substitutes whereas labor and traditional capital are complements. The model replicates the dynamics of the observed functional income distribution in the US during the 1965-2015 period. Counterfactual experiments suggest that the fall in the labor share would have been significantly smaller if labor and capital income tax rates had remained at their respective level of the 1960s.
Keywords: D33; E62; O41; J11; J20; 330; functional income distribution; labor income share; income taxes; automation capital; demography; growth